Catalytic Nanoreactors of Au@Fe3O4 Yolk-Shell Nanostructures with Various Au Sizes for Efficient Nitroarene Reduction - Lin, Fang-hsin; Doong, Ruey-an (My University, 2017)
Au@Fe3O4 yolk shell nanocatalysts based on the thermal decomposition of iron pentacarbonyl in the presence of 2.5-10-nm Au core nanoparticles were successfully fabricated for the catalytic reduction of nitroarenes. The particle sizes of the Au@Fe3O4 nanostructures were in the range 8-15 nm, with Fe3O4 shell layer thicknesses of 2.0-2.4 nm. The Fe3O4 layer not only can form a magnetic shell for recovery but also enables the protection of the catalytic activity of the Au core nanoparticles toward the reduction of nitrobenzene derivatives including 2-nitrophenol, 4-nitrophenol, 4-nitrotoluene, and 1-chloro-4-nitrobenzene in the presence of NaBH4. The catalytic performance of Au@Fe3O4 is highly dependent on the particle size of the Au core materials and the substituent groups of the nitroarenes. The reduction rates of nitroarenes with electron-withdrawing groups were found to be 2.3-2.6 times higher than those of nitroarenes with electron-donating groups. In addition, the reduction of nitroarenes by the Au@Fe3O4 yolk shell nanocatalysts was found to be a surface-mediated reaction, and the relationship rate and the initial NaBH4 concentration was found to follow Langmuir Hinshelwood kinetics. Moreover, the yolk shell nanoparticles showed good separation ability and reusability, as they could be repeatedly applied for the nearly complete reductions of 4-nitrophenol and 1-chloro-4-nitrobenzene for at least five successive cycles. These unique properties make Au@Fe3O4 nanocatalysts an ideal platform for tailoring yolk shell nanoreactors with various active materials and also for studying various heterogeneous catalytic processes.